Explorations of structure and choice in taxing capital gains in New Zealand : tax practitioners' perspectives / Alvin Cheng and Sue Yong - Cheng, Alvin; Yong, Sue (Research Management Institute (RMI), 2011)
This paper explored the tax practitioners 'views on taxation of capital gains in New Zealand. An 8-page questionnaire was sent to 507 tax practitioners to discuss various tax issues relating to capital gains. The tax issues were taxation on property, rollover relief, indexation and several others. The findings overwhelmingly showed that a capital gains tax (CGT) was not supported by most tax practitioners, A plausible reason for the strong opposition to a CGT by the tax practitioners was attributable to the increased compliance costs and the interpretation surrounding the CGT legislation. The absence of a comprehensive CGT in New Zealand can potentially provide lucrative business opportunities for tax practitioners by advising their clients to convert taxable incomes into tax free capital gains. However there was no empirical evidence to suggest that the loss of tax revenue was due to such tax planning activities. This might be due to the uniqueness of certain types of gains, which would normally be regarded as capital in nature inforeign jurisdictions deemed to be income in New Zealand.